2014
DOI: 10.3354/ame01695
|View full text |Cite
|
Sign up to set email alerts
|

Picoeukaryote distribution in relation to nitrate uptake in the oceanic nitracline

Abstract: We investigated the relationship between picoeukaryote phytoplankton (< 2 µm) and the deep layer of new production (NO 3 − uptake) in the nitracline of the eastern subtropical North Atlantic Ocean. Indices of NO 3 − uptake kinetics obtained within the lower 15% of the euphotic zone demonstrate that subsurface NO 3 − uptake maxima are coincident with localised peaks in maximum uptake rates (V max ) and, crucially, with maximum picoeukaryote abundance. The mean rate of NO 3 − utilization at the nitracline is typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 105 publications
4
16
0
Order By: Relevance
“…Differences in relative abundances of phytoplankton groups between Z u and Z l showed a clear two-tiered vertical niche partition, with Prochlorococcus and Synechococcus reaching maximum abundances in the Z u and PPE achieving maximum abundances in the Z l . This vertical distribution has been well documented in other regions, and is thought to be characteristic of highly stratified oligotrophic systems (Dore et al, 2008;Painter et al, 2014;Partensky et al, 1996). Based on estimates from HPLC data, larger organisms such as diatoms and dinoflagellates were present in very low abundance along the transect, in comparison to small-sized phytoplankton.…”
Section: Distribution Of Pigments and Photo Acclimation In Different mentioning
confidence: 52%
“…Differences in relative abundances of phytoplankton groups between Z u and Z l showed a clear two-tiered vertical niche partition, with Prochlorococcus and Synechococcus reaching maximum abundances in the Z u and PPE achieving maximum abundances in the Z l . This vertical distribution has been well documented in other regions, and is thought to be characteristic of highly stratified oligotrophic systems (Dore et al, 2008;Painter et al, 2014;Partensky et al, 1996). Based on estimates from HPLC data, larger organisms such as diatoms and dinoflagellates were present in very low abundance along the transect, in comparison to small-sized phytoplankton.…”
Section: Distribution Of Pigments and Photo Acclimation In Different mentioning
confidence: 52%
“…The close relationship between DCM layers and picoeukaryote abundance reported here has been previously described at the western boundary of the southern Atlantic Gyre (Zubkov et al, 2000) and close to its center (Tarran, Heywood & and, 2006). Painter et al (2014) observed maximum picoeukaryote abundance coinciding with maximum NO 3 uptake rates, near the nitracline, which indicate that these populations may be major players for production in the deeper layers of the euphotic zone, fueling the downward flux of carbon to the ocean interior through the formation of aggregates (Lomas & Moran, 2011). This dominance at the DCM could be linked to their better adaptation to low light levels compared to larger phytoplankton and Synechococcus (Worden & Not, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…The works by Fawcett et al (2011Fawcett et al ( , 2014 and Painter et al (2014), all conducted in the subtropical North Atlantic, provide evidence that PPE derive a significant fraction of their cellular nitrogen demand via assimilation of nitrate. However, it is not clear how applicable these results are to plankton nutritional dynamics at Station ALOHA in the subtropical North Pacific.…”
Section: Discussionmentioning
confidence: 99%